VIOLENCE AGAINST LISBETH SALANDER IN STIEG LARSSON’S THE GIRL WITH THE DRAGON TATTOO - Mariano Durman Natung; Emilia Tetty Harjani (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2021)
This research analyzed the violence against Lisbeth Salander in Stieg Larsson’s The Girl with the Dragon Tattoo. It used the feminist literary approach by Tyson Lois and the theory of violence by Nancy Crowel and Ann Burgess. The objectives of this research were to find the forms of violence happened to Lisbeth Salander, the effects of violence on her life, and how Lisbeth Salander resisted the violence that she experienced. The result of this research indicated that there were four forms of violence experienced by Lisbeth Salander. They were physical violence, sexual violence, emotional violence, and economic violence. There were also effects from the violence she experienced that affected her physical and her psychological condition. Even though the violence experienced by Lisbeth Salander gave negative impacts on her life more, it also gave positive impact. Her experiences with violence gave her motivation to survive. It can be seen through her resistance against the violence that happened to her. Finally, she became an independent woman.